Relações da atividade agropecuária com parâmetros físicos químicos da água - Carvalho, Adriana Rosa; Schlittler, Flávio Henrique Mingante [UNESP]; Tornisielo, Valdemar Luiz (Sociedade Brasileira de Química, 2000)
Water Quality Index (WQI) was used during summer and winter of 1994 and 1995 in the final section of Onça and Feijão streams, downstream Broa Reservoir (São Carlos/SP) to evaluate agricultural and catlleman effects. In Onça stream water quality was acceptable in winter and inappropriate to conventional treatment in the summer. In Feijão stream the water had an excellent quality in winter and good in the summer. A MANOVA (Multivariate Analysis of Variance) has used to discriminate seasons and streams. Correlation (p<0,05) among the variables was tested. Water temperature, turbidity, pH and fecal bacteria are highly correlated and can be one of the factors that cause WQI change by seasons.
Influence of cattle ranching and agricultural activities on physical chemical parameters of water
Keywords: water quality; grazing; agriculture; limnology; physic-chemical parameters